Analiza poznavanja in uporabe metod presoje investicijskih projektov v strojništvu - Pšunder, Igor (Strojniški vestnik, 2007)
Research done in the USA and the UK has shown that, with the increased use of computers and electronic spreadsheets, the use of these investment project evaluation methods that are based on discounted cash flow has increased. However, theoretical findings about these methods show that they have numerous limitations, and ignorance of these limitations can lead to false results as well as false conclusions about investments and investment projects. This paper shows the research results acquired from project managers of Slovene companies. Their personal opinions about investment project evaluation methods and knowledge of the methods faults were studied inthe research. Methods based on discounted cash flow as well as single-period methods of investment evaluation and investment projects were used. During the analysis of the results the situation in the field of mechanical engineering was treated separately and compared with other technical and non-technical sciences. Research has shown that experts dealing with investment project evaluation who have a degree in the field of mechanical engineering more often use discounted cash-flow methods for investment project evaluation than do experts of other technical sciences, but approximately as often as experts in economics and similar sciences. We were able to conclude that experts with education in mechanical engineering are more than usually familiar with the flaws in investment project evaluation methods, but at the same time, only half of them know the multiple internal rate of return, which is the most commonly mentioned fault of the internal rate of return method. Only one-third of experts are familiar with result deformation due to a disregard for the time component of payments in the payback period method.
Keywords: strojništvo; investicijski projekti; evalvacija